La Literatura Infantil, para potenciar el aprendizaje de Lengua y Literatura de los niños y niñas del quinto año básico de la Unidad Educativa Riobamba, del Cantón Riobamba, Provincia de Chimborazo, durante el año Lectivo 2015 -2016 - Pérez Lluay, Jessica Liliana (2016)
This research is the realization of a diagnosis in the Riobamba Educational Unit to identify whether teachers use children's literature to promote language learning and literature in children aged 9 to 10 years where the problem exists at macro, medium and micro level raised by justifying the importance, relevance, feasibility and the beneficiaries arc children in fifth grade, where the objectives arc also looking for was considered to be demonstrated solution to the research problem, continuing the analysis of the theoretical framework that could define concepts of the two variables that tell us that literature helps children develop skills of creative thinking, the same which permits us to solve problems and make decisions. Creativity is the thinking skill because it intuition, imagination, logic and imagination combined. The method of this research is descriptive, using according to their field research design, allowing critically analyze the theoretical foundations of children's literature and sensitivity in children, whether teachers use reading as a means to strengthen language and literature, identify what strategies are needed to develop the imagination in children education, followed by analysis and interpretation of results, also including the suggestions and recommendations to allow students to enrich the literary genres to improve their learning process. Finally, the respective annex is attached.